Village Asset Management in Toll Road Development: An Analysis of Permendagri No. 3 of 2024 Amending Permendagri No. 1 of 2016 in Central Java Province - Ratuningnagari, Ayu Melati; Muhammad Junaidi; Soegianto Soegianto; Sudarmanto, Kukuh (Universitas Semarang, 2025)
This study aims to analyze the management of village assets affected by toll road construction in Central Java Province based on Minister of Home Affairs Regulation (Permendagri) Number 3 of 2024, which amends Permendagri Number 1 of 2016 on Village Asset Management, as well as to identify the obstacles encountered in its implementation. The research employs a normative juridical method with a conceptual approach, is descriptive-analytical in nature, and relies on secondary data consisting of primary, secondary, and tertiary legal materials analyzed qualitatively. The findings reveal that the management of village assets affected by toll road development is carried out through stages of inventory, planning, procurement, disposal, and transfer, guided by the principles of effectiveness, transparency, accountability, and legal certainty as stipulated in Articles 10, 11, and 19 of Permendagri Number 3 of 2024. Major challenges include difficulties in finding substitute land, unclear technical procedures, and discrepancies in asset valuation, often leading to disputes that must be settled through court proceedings. The novelty of this study lies in its focus on village assets—particularly treasury land (tanah kas desa)—which has been largely overlooked in previous research on land acquisition for toll roads, as most prior studies emphasize individual land rights under Law Number 2 of 2012. Accordingly, this research underscores the need for strengthened technical regulations and inter-institutional coordination to ensure legal certainty, protect village rights, and promote fair and sustainable asset management in the context of toll road development.